Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.14814/phy2.12735
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory roles of CTRP3 in endotoxemia and metabolic stress

Abstract: C1q/TNF‐related protein 3 (CTRP3) is a secreted hormone that modulates hepatic glucose and lipid metabolism. Its circulating levels are reduced in human and rodent models of obesity, a metabolic state accompanied by chronic low‐grade inflammation. Recent studies have demonstrated an anti‐inflammatory role for recombinant CTRP3 in attenuating LPS‐induced systemic inflammation, and its deficiency markedly exacerbates inflammation in a mouse model of rheumatoid arthritis. We used genetic mouse models to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 59 publications
4
41
1
Order By: Relevance
“…Specifically, CTRP3 is an anti-inflammatory adipokine which inhibits toll-like receptor (TLR) and nuclear factor κB (NF-κB) signaling pathway and also reduces IL-6 and TNF-α secretion [29,30]. Also, Peterson et al have shown an immunomodulatory role for CTRP3 in systemic and chronic inflammation associated with insulin resistance and obesity, but no role in antagonizing LPS induced inflammation in mice model [31]. A more recent study reported a decrease in CTRP3 serum levels in stable and unstable angina pectoris patients [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CTRP3 is an anti-inflammatory adipokine which inhibits toll-like receptor (TLR) and nuclear factor κB (NF-κB) signaling pathway and also reduces IL-6 and TNF-α secretion [29,30]. Also, Peterson et al have shown an immunomodulatory role for CTRP3 in systemic and chronic inflammation associated with insulin resistance and obesity, but no role in antagonizing LPS induced inflammation in mice model [31]. A more recent study reported a decrease in CTRP3 serum levels in stable and unstable angina pectoris patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Independent association between CTRP3 and CAD can be explained by the effect of CTRP3 on different aspects of atherosclerosis, such as inflammation and metabolic disorders. However, we found no correlation between CTRP3 and inflammatory markers, but association between CTRP3 and CAD may be justified by potent anti-inflammatory effect of CTRP3 on inhibiting inflammatory signaling pathways, reducing secretion of inflammatory mediators [29,37] and its favorable role in systemic and chronic inflammation associated with insulin resistance and obesity [31], as well as, cardio-protective effects of CTRP3 [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue immune response plays amajor role in the development of the chronic proinflammatory state (22, 26). Whereas, CTRP3 is a potential anti-inflammatory mediator, and is negatively associated with the proinflammatory cytokines TNF, IL-6, and C-reactive protein (5, 11, 12, 14, 48, 50, 52, 65, 83). In animal models, diet-induced obesity results in decreased CTRP3 levels concurrent with an elevation in TNF and IL-6 (50).…”
Section: Inflammationmentioning
confidence: 99%
“…Combined, these data show promise for the use of CTRP3 and CTRP3-mediated pathways as a potential anti-inflammatory mediator. However, neither chronic CTRP3 deficiency nor overexpression altered the inflammatory response to a sublethal challenge to LPS (48), indicating that CTRP3 levels need to be regulated transiently to demonstrate an anti-inflammatory effect. Regardless, the potential use of CTRP3 as an inhibitor of inflammation needs to be examined in more detail.…”
Section: Inflammationmentioning
confidence: 99%
“…Regulates glucose and lipid metabolism regulates systemic inflammation in obesity and insulin resistance; modulates mitochondrial biogenesis; attenuate liver fibrosis; biomarker for diabetic retinopathy; negative regulator of osteoclastogenesis; independent predictor for atherosclerosis [47,[56][57][58][59][60] 4 Hepatic cells Modulates energy metabolism; novel nutrient-responsive central regulator of food intake and energy balance; reduces colitis; suppresses the pyroptosis of trophoblasts derived from rats with preeclampsia [61][62][63] 5 Adipose tissue, ocular tissue…”
Section: Ctrps Perturbations and Metabolismmentioning
confidence: 99%